Studi Meta-Analisis Model Pembelajaran Inquiry Terbimbing dalam Pembelajaran Fisika - Nurhasanah Nurhasanah; Dasmo Dasmo (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This study aims to analyze the influence of the guided inquiry learning model in physics learning through the overall effect size, based on the dependent variable and region. This research uses a descriptive method with a meta-analysis approach to the results of scientific research publications in national electronic journals. There are 11 national journals that fit the research category. The results showed that overall learning using the guided inquiry model could improve students' physics learning outcomes with the effect size of 0.487 from the control group. Meanwhile, based on the distribution of regions in Indonesia, an average effect size of 0.527 is obtained and based on the dependent variable an effect size is obtained of 0.425. These three results indicate a large effect size guided inquiry learning model in physics learning. This shows that the guided inquiry learning model can provide a more effective effect and is suitable for use in learning physics.